Differences in Students' Perceptions of Chemistry Learning Using Google Classroom and Discord - Egi Syahrah Anggraeni; Linawati; Sukemi; Sri Lestari (Jurnal Penelitian Pendidikan IPA, 2026)
Learning management system (LMS) applications such as Google Classroom and Discord help an online learning. The objectives of research are to knowing the differences on students’ perceptions toward chemistry learning using Google Classroom and Discord. The type of research used is retrospective comparative quantitative that utilizes documentation of student perception data that has been collected previously. Samples of this study were 68 respondents from tenth grade students of SMAN 2 Samarinda in the academic year of 2020/2021 who were taught using Google Classroom and 74 respondent majoring in Mathematics and Natural Sciences at SMAN 13 Samarinda in the academic year of 2020/2021 who were taught using Discord. The method of data collecting by documentation technique and the data analyzed by using independent t-test and mann withney u. The results showed that the t-test obtained 0.032 < 0.05, there is a significant difference between students' perceptions toward chemistry learning using Google Classroom and Discord, but there is no difference in perception results when viewed from the gender of each platform (Sig. (2-tailed) value of 0.821 (for Google Classroom) and 0.314 (for Discord)). Students' perceptions toward chemistry learning using Google Classroom are better than that of using Discord.